Evaluating the quality experience of ecotourist in Taman Negara Pahang - Khairudin, Ahmad Danial; Abd Rahman, Nur Hidayah (IOP Publishing Ltd, 2020)
Tourists that travel to a destination will gain different kinds of experiences due to several conditions of a destination. To identify what are the Quality Experience that a tourist gained, certain characteristics of experiences will be determined by using Memorable Tourism Experience (MTE). Taman Negara Pahang a National Park in Malaysia which rich in the natural habitat which is considered as an ecotourism destination. Thus, the purpose of this study is to understand the Quality Experience of eco-tourist in Taman Negara Pahang by using the Memorable Tourism Experience (MTE). This study will be focusing on the main objective which is to determine the most influential Quality Experience of eco-tourists in Taman Negara Pahang. This study is a quantitative study and an online survey was used as the data collection instrument for the 130 respondents. This study shows that the preferred Quality Experience of eco-tourist is Hedonism while the least preferred Quality Experience is Local Culture. This study contributes to identify the Quality Experience of eco-tourist gained after they have visited an ecotourism destination. Therefore, the results of this study can offer a quality contribution towards any responsible parties to manage Taman Negara Pahang in terms of services, and management.